3D printed implant surgical guides with internally routed irrigation for temperature reduction during osteotomy preparation: A pilot study. Issue 5 (27th November 2021) - Teich, Sorin; Bocklet, Michael; Evans, Zachary; Gutmacher, Zvi; Renne, Walter
Abstract: Objective: The purpose of this study was to test a novel through‐the‐guide means of irrigation in an in‐vitro bovine bone model and to explore the method clinical applicability. Materials and Methods: Surgical guides were designed to fit over five fresh bovine samples. Control osteotomy sites were compared to experimental sites irrigated through a 3D printed surgical guide with customized channels that direct the coolant toward the interface of the alveolar crest and drill. Temperature was measured during surgery with thermocouples located at 3 and 6 mm from the crestal height of the bone, and with an infrared thermal camera taking direct temperature readings from a window cut into axial wall at 9 mm from the crestal height of the ridge. Results: Incorporation of routed irrigation significantly decreased heat generation, keeping temperature consistently below 47°C. A clinical case illustrates the method applicability using standard implant planning software, 3D printing technology, and regular implant armamentarium. Conclusions: The in‐vitro analysis shows that this method mitigates temperature increase caused by static surgical guide irrigation blockade at the osteotomy site. This technique can be incorporated in the surgical guide design using commercially available software and 3D printing technology and has immediate applications in practice. Clinical Significance: The in‐vitro analysis shows that this method can significantly mitigate the temperature increase caused by static surgical guide irrigation blockade at the osteotomy site. This technique also has the advantage that it can be incorporated in the digital surgical guide design using commercially available software and 3D printing technology. The method has immediate applications in practice, and especially in the treatment of edentulism in esthetic zone where use of guided surgery for implant placement is crucial in obtaining consistent results.